Quality of Life, Physical and Mental Health of Family Caregivers of Dependent People with Complex Chronic Disease: Protocol of a Cohort Study - Marfil Gómez, Raquel; Morales-Puerto, Marta; León-Campos, Álvaro; Morales-Asencio, José Miguel; Morilla-Herrera, Juan Carlos; Timonet Andreu, Eva María; Cuevas-Fernández-Gallego, María Magdalena; Martí-García, Celia; López-Leiva, María Inmaculada; García-Mayor, Silvia (MDPI, 2020)
Abstract: Background: informal caregivers have a high risk of su ering from diseases derived from the chronic stress to which they are subjected for their dedication to the care of their relatives. Such stress has a direct influence on the person cared for, mainly a ecting the quality of their care. Therefore, the aim of the present study is to assess the association of caregiving on physical and mental perceived health in family caregivers of dependent adults with complex chronic diseases. Methods: a prospective longitudinal cohort study, with a follow-up period of 36 months (HUELLA cohort). The exposed cohort will be formed by family caregivers of dependent patients with complex chronic pathologies. The unexposed cohort will be taken from the general population adjusted for age, sex and health. Outcome variables will include attendance to health services, consumption of psychoactive drugs, dedication to care (only in exposed cohort), concession of the Act on Promotion of Personal Autonomy and Care for dependent persons (exposed only), perceived physical and mental health, depression level, burden level and new diagnosis of chronic pathology of the caregiver during the study. Results: the expected results will be applicable and will incorporate improvements to the usual health system clinical practice, providing feedback to professionals dedicated to the provision, planning and design of services to family caregivers, as well as to groups and organizations of caregivers. Conclusions: investments in preventing low-quality informal care are key, mainly through early identification and interventions to support caregivers who su er from stress, anxiety or depression.
Keywords: Cuidadores - Salud mental; Estrés (Psicología) - Control; Enfermos crónicos - Cuidado; Nurses; Nursing; Caregivers; Quality of life; Mental health; Complex chronic disease